Radiocesium contamination and estimated internal exposure doses in edible wild plants in Kawauchi Village following the Fukushima nuclear disaster - Tsuchiya, Rimi (PLoS One, 2017)
Kawauchi Village, in Fukushima Prefecture, is located within a 30-km radius of the nuclear disaster site of the Fukushima Daiichi Nuclear Power Plant (FDNPP). “Sansai” (edible wild plants) in this village have been evaluated by gamma spectrometry after the residents had returned to their homes, to determine the residents’ risk of internal exposure to artificial radionuclides due to consumption of these plants. The concentrations of radiocesium (cesium-134 and cesium-137) were measured in all 364 samples collected in spring 2015. Overall, 34 (9.3%) samples exceeded the regulatory limit of 100 Bq/kg established by Japanese guidelines, 80 (22.0%) samples registered between 100 Bq/kg and 20 Bq/kg, and 250 (68.7%) registered below 20 Bq/kg (the detection limit). The internal effective doses from edible wild plants were sufficiently low (less than 1 mSv/y), at 3.5±1.2 μSv/y for males and 3.2±0.9 μSv/y for females (2.7±1.5 μSv/y for children and 3.7±0.7 μSv/y for adults in 2015). Thus, the potential internal exposure doses due to consumption of these edible wild plants were below the applicable radiological standard limits for foods. However, high radiocesium levels were confirmed in specific species, such as Eleutherococcus sciadophylloides (“Koshiabura”) and Osmunda japonica (Asian royal fern, “Zenmai”). Consequently, a need still might exist for long-term follow-up such as environmental monitoring, physical and mental support to avoid unnecessary radiation exposure and to remove anxiety about adverse health effects due to radiation. The customs of residents, especially the “satoyama” (countryside) culture of ingesting “sansai,” also require consideration in the further reconstruction of areas such as Kawauchi Village that were affected by the nuclear disaster.